Stereotactically Injected Kv1.2 and CASPR2 Antisera Cause Differential Effects on CA1 Synaptic and Cellular Excitability, but Both Enhance the Vulnerability to Pro-epileptic Conditions - Kirschstein, Timo; Sadkiewicz, Erika; Hund-Göschel, Gerda; Becker, Juliane; Guli, Xiati; Müller, Steffen; Rohde, Marco; Hübner, Dora-Charlotte; Brehme, Hannes; Kolbaske, Stephan; Porath, Katrin; Sellmann, Tina; et al. (Frontiers in Synaptic Neuroscience, 2020)
Purpose: We present a case of voltage-gated potassium channel (VGKC) complex antibody-positive limbic encephalitis harboring autoantibodies against Kv1.2. Since the patient responded well to immunotherapy, the autoantibodies were regarded as pathogenic. We aimed to characterize the pathophysiological role of this antibody in comparison to an antibody against the VGKC-associated protein contactin-associated protein-2 (CASPR2). Methods: Stereotactic injection of patient sera (anti-Kv1.2-associated limbic encephalitis or anti-CASPR2 encephalopathy) and a control subject was performed into the hippocampus of the anesthetized rat in vivo, and hippocampal slices were prepared for electrophysiological purposes. Using extra- and intracellular techniques, synaptic transmission, long-term potentiation (LTP) and vulnerability to pro-epileptic conditions were analyzed. Results: We observed that the slope of the field excitatory postsynaptic potential (fEPSP) was significantly increased at Schaffer collateral-CA1 synapses in anti-Kv1.2-treated and anti-CASPR2-treated rats, but not at medial perforant path-dentate gyrus synapses. The increase of the fEPSP slope in CA1 was accompanied by a decrease of the paired-pulse ratio in anti-Kv1.2, but not in anti-CASPR2 tissue, indicating presynaptic site of anti-Kv1.2. In addition, anti-Kv1.2 tissue showed enhanced LTP in CA1, but dentate gyrus LTP remained unaltered. Importantly, LTP in slices from anti-CASPR2-treated animals did not differ from control values. Intracellular recordings from CA1 neurons revealed that the resting membrane potential and a single action potential were not different between anti-Kv1.2 and control tissue. However, when the depolarization was prolonged, the number of action potentials elicited was reduced in anti-Kv1.2-treated tissue compared to both control and anti-CASPR2 tissue. In contrast, polyspike discharges induced by removal of Mg2+ occurred earlier and more frequently in both patient sera compared to control. Conclusion: Patient serum containing anti-Kv1.2 facilitates presynaptic transmitter release as well as postsynaptic depolarization at the Schaffer-collateral-CA1 synapse, but not in the dentate gyrus. As a consequence, both synaptic transmission and LTP in CA1 are facilitated and action potential firing is altered. In contrast, anti-CASPR2 leads to increased postsynaptic potentials, but without changing LTP or firing properties suggesting that anti-Kv1.2 and anti-CASPR2 differ in their cellular effects. Both patient sera alter susceptibility to epileptic conditions, but presumably by different mechanisms.